2019
DOI: 10.1128/msphere.00228-19
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Profiling of the Enterococcus faecalis Transcriptional Response to Teixobactin Reveals CroRS as an Essential Regulator of Antimicrobial Tolerance

Abstract: Teixobactin is a new antimicrobial of significant interest. It is active against a number of multidrug-resistant pathogens, including Staphylococcus aureus and Enterococcus faecalis, with no reported mechanisms of teixobactin resistance. However, historically, mechanisms of resistance always exist and arise upon introduction of a new antimicrobial into a clinical setting. Therefore, for teixobactin to remain effective long term, we need to understand how mechanisms of resistance could develop. Here we demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Teixobactin, a new antimicrobial agent has documented activity against S. aureus and Enterococcus faecalis without resistance. A study which reported on the transcriptional response of E. faecalis to teixobactin levels identified development of intrinsic tolerance to high concentrations of the same (through deletion of croRS ), and this is generally considered a precursor for the development of resistance [ 70 ]. Besides known mechanisms, involving differential expression of genes targeted by antibiotics, and xenobiotic efflux transporters, emerging studies have the potential to reveal regulatory circuits that respond to different toxic stimuli and other compensatory mechanisms.…”
Section: Metagenomic Approaches For Resistance Surveillancementioning
confidence: 99%
“…Teixobactin, a new antimicrobial agent has documented activity against S. aureus and Enterococcus faecalis without resistance. A study which reported on the transcriptional response of E. faecalis to teixobactin levels identified development of intrinsic tolerance to high concentrations of the same (through deletion of croRS ), and this is generally considered a precursor for the development of resistance [ 70 ]. Besides known mechanisms, involving differential expression of genes targeted by antibiotics, and xenobiotic efflux transporters, emerging studies have the potential to reveal regulatory circuits that respond to different toxic stimuli and other compensatory mechanisms.…”
Section: Metagenomic Approaches For Resistance Surveillancementioning
confidence: 99%
“…MIC is defined as the lowest concentration required for the antibacterial agents to inhibit ≥90% of bacterial growth [23,24]. In this study, the MIC value of L -Chg 10 -teixobactin on E. faecalis ATCC 29212 and ATCC 47077 strains was lower than the 2 µg/mL reported by Darnell et al [25] on a different strain of E. faecalis, i.e., strain JH2-2; it was slightly higher than the 0.5 µg/mL reported by Ling et al [16] on vancomycin-resistant E. faecalis [16,25]. Two plausible explanations may account for the differences, including the use of different teixobactin or its analogues as the tested drug and the different strains of E. faecalis studied.…”
Section: Discussionmentioning
confidence: 51%
“…62,63 Previous E. faecalis transcriptome studies display a downregulation of ribosomal proteins when cell wall synthesis is inhibited following antimicrobial treatment. 64,65 In the global proteome data analyzed here, proteins related with translation are decreased in abundance specifically after ceftriaxone treatment (which inhibits cell wall synthesis by preventing cross-linking of peptidoglycan outside the cytoplasmic membrane) and this could result in the production of incomplete proteins in the cytoplasm for processing by SsrA/ SmpB. These results suggest that this quality control and degradation pathway is controlled through phosphorylation.…”
Section: Cell Wall-active Antimicrobial-modulated Phosphorylationmentioning
confidence: 78%